Ventral tegmental area deep brain stimulation for chronic cluster headache: Effects on cognition, mood, pain report behaviour and quality of life. (August 2019) - Cappon, Davide; Ryterska, Agata; Lagrata, Susie; Miller, Sarah; Akram, Harith; Hyam, Jonatham; Zrinzo, Ludvic; Matharu, Manjit; Jahanshahi, Marjan
Background: Deep brain stimulation in the ventral tegmental area (VTA-DBS) has provided remarkable therapeutic benefits in decreasing headache frequency and severity in patients with medically refractory chronic cluster headache (CH). However, to date the effects of VTA-DBS on cognition, mood and quality of life have not been examined in detail. Methods: The aim of the present study was to do so in a case series of 18 consecutive patients with cluster headache who underwent implantation of deep brain stimulation electrodes in the ventral tegmental area. The patients were evaluated preoperatively and after a mean of 14 months of VTA-DBS on tests of global cognition (Mini Mental State Examination), intelligence (Wechsler Abbreviated Scale of Intelligence), verbal memory (California Verbal Learning Test-II), executive function (Delis–Kaplan Executive Function System), and attention (Paced Auditory Serial Addition Test). Depression (Beck Depression Inventory and Hospital Anxiety and Depression Rating Scale-D), anxiety (Hospital Anxiety and Depression Rating Scale-A), apathy (Starkstein Apathy Scale), and hopelessness (Beck Hopelessness Scale) were also assessed. Subjective pain experience (McGill Pain Questionnaire), behaviour (Pain Behaviour Checklist) and quality of life (Short Form-36) were also evaluated at the same time points. Results: VTA-DBS resulted in significant improvement of headache frequency (from a mean of five to two attacks daily, p < .001) and severity (from mean Verbal Rating Scale [VRS] of 10 to 7, p < .001) which was associated with significant reduction of anxiety (from mean HADS-A of 11.94 to 8.00, p < .001) and help-seeking behaviours (from mean PBC of 4.00 to 2.61, p < .001). VTA-DBS did not produce any significant change to any tests of cognitive function and any other outcome measures (BDI, HADS-D, SAS, BHS, McGill Pain Questionnaire, Short Form-36). Conclusion: We confirm the efficacy of VTA-DBS in the treatment of medically refractory chronic cluster headache. The reduction of headache frequency and severity was associated with a significant reduction of anxiety. Furthermore, the result suggests that VTA-DBS for chronic cluster headache improves pain-related help-seeking behaviours and does not produce any change in cognition.